Botulism: Pathogenesis, Diagnosis and Prevention - natalia, lili (Indonesian Animal Sciences Society, 2012)
Botulism is a potential lethal disease in animals as well as in human, a neuroparalytic disease caused by Clostridium botulinum toxin. C. botulinum is widely distributed in the soil and vegetation, intestinal contents of mammals, birds and fish. Eight types of C. botulinum (A, B, C1, C2, D, E, F, G) have been recognized, each elaborating an immunologically distinct form of toxin. Botulinum neurotoxins are the most powerful biological toxins known and in some countries they have been studied and developed as biological weapon. The medical aspects of the toxin were also developed for therapeutic uses in human diseases. The spores of C. botulinum are relatively heat resistant and in contrast to the spores, botulinum toxin is relatively heat labile. Botulinum toxins are inactivated by their antitoxins. Botulinum toxin produces clinical manifestations when either inhaled or ingested. After toxin is absorbed, it enters the bloodstream and travels to peripheral cholinergic synapses, primarily the neuromuscular junction. Once at these sites, botulinum toxin is internalized and enzymatically prevents the release of acteylcholine leads to paralysis. Laboratory diagnoses for botulism should include isolating C. botulinum and detecting of toxin in the patient. Rapid and sensitive detection of all types of botulinum toxin are needed. Cases of botulism in Indonesia were found primarily in poultry and many cases were suspected and remained undiagnosed. Cases of botulism were suspected affecting cattle in East Java and serologically results showed positive to C. botulinum type C. The botulismus prevention using vaccine induced a strong antibody response and could be remained protective for 12 months, while botulism treatment in animals is usually ineffective. Key words: Botulism, Clostridium botulinum, toxin, diagnosis, prevention